2023
DOI: 10.1039/d3cc02236f
|View full text |Cite
|
Sign up to set email alerts
|

Accessing unnatural α-amino acids with tetrasubstituted stereogenic centersviacatalytic enantioselective reactions of ketimine-type α-iminoesters/α-iminoamides

Abstract: Catalytic enantioselective synthesis methodologies have been actively explored and developed owing to the significance of chiral molecules and their utilities. In particular, unnatural α-amino acids with tetrasubstituted stereogenic carbon centers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 213 publications
0
3
0
Order By: Relevance
“…Overall, these advances via addition at ketimines provided more structural diversity of afforded α,α-disubstituted α-AAs through reaction with previously challenging reagents such as styrenes and allenes. Moreover, during the preparation of our manuscript, another extensive review about the catalytic enantioselective reactions of ketimine-type α-iminoesters/α-iminoamides to access unnatural α-AAs was published 82 .…”
Section: Synthesis Of αα-Disubstituted Amino Acids Via the C-c Bond F...mentioning
confidence: 99%
“…Overall, these advances via addition at ketimines provided more structural diversity of afforded α,α-disubstituted α-AAs through reaction with previously challenging reagents such as styrenes and allenes. Moreover, during the preparation of our manuscript, another extensive review about the catalytic enantioselective reactions of ketimine-type α-iminoesters/α-iminoamides to access unnatural α-AAs was published 82 .…”
Section: Synthesis Of αα-Disubstituted Amino Acids Via the C-c Bond F...mentioning
confidence: 99%
“…We hypothesized that α-thio-substituted chiral aminonitriles could be obtained by using α-iminonitriles as a novel precursor of amino acid derivatives (Scheme d, right). Nevertheless, methods for the stereoselective construction of a chiral amines-bearing tetrasubstituted carbon center via asymmetric nucleophilic addition reaction to preformed ketimines are still limited, mainly due to the challenges associated with the formation of a highly hindered chiral center . Our research group recently reported the first enantioselective reaction of N -cyanoimines to construct β-amino acid derivatives in the use of hydrogen-bonding-donor (HBD) catalysts (Scheme c) .…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, β-electron-withdrawing group (ester or carbonyl)-tethered acrylamide usually acts as a N , C α -1,3-synthon in chiral amine-catalyzed asymmetric cascade aza-Michael/Michael reaction with α, β-unsaturated aldehydes, as well as Lewis base-catalyzed formal [3 + 2]-annulation reactions with nitro-heteroarenes or isocyanates . On the other hand, cyclic N -sulfonyl imines exhibit versatile reaction activity in organocatalytic, metal-catalyzed, or radical-mediated cycloaddition reactions, which provide straightforward, powerful, and atom-economical methods to a wide range of diverse pharmacologically sultam or sulfamidate-fused nitrogen-containing heterocycles . Based on our achievements in the field of heterocyclic chemistry involving N -alkoxy α-halohydroxamate or acrylamide, and in line with our continuous efforts in annulation reactions, we have successfully established an Et 3 N-catalyzed aza-Mannich reaction triggered cascade annulation reaction of β-oxo-acrylamides with cyclic N -sulfonyl imines, leading to the formation of highly functionalized sulfamide-fused imidazolidinone derivatives (Scheme f).…”
Section: Introductionmentioning
confidence: 99%